Single Leg Stance para a avaliação do equilíbrio estático em idosos com doença pulmonar obstrutiva crônica (dpoc): comparações entre as pernas direita e esquerda, confiabilidade e características associadas - Rodrigues, Ronikelson (2024)
Introduction: Chronic obstructive pulmonary disease (COPD) is a disease that not only affects the lungs, but also causes several systemic manifestations, such as balance problems, which can lead to falls. Several tests have been proposed to assess balance in individuals with COPD. The single leg stance (SLS) is a quick and simple test to assess static balance, however there is no robust evidence for reliability between results performed on the same day and associated factors. Objective: To analyze aspects related to SLS not yet specifically explored in the literature in elderly people with COPD, such as the comparison between the results of each leg, reliability on the same day, and factors associated with the results of each leg. Methods: This is a cross-sectional study that used the baseline assessment of a study to predict negative outcomes in individuals with COPD. Elderly people with COPD in stable condition, followed at the pulmonology outpatient clinic of a public university hospital, were included. Sociodemographic (e.g., age, sex), anthropometric (e.g., weight, height) and clinical data (e.g., Charlson comorbidity index - ICC), degree of dyspnea (modified Medical Research Council scale - mMRC), and status (COPD assessment test – CAT)were collected. In addition, simple physical function tests were used: SLS, performed three times on each leg with a maximum time of 60 seconds for each attempt, timed up & go (TUG) and 1-minute sitto- stand (1MSTS). Results: 62 elderly people with COPD were included (mean age 71 years, 55% male, 45% GOLD 3). For 79% of the sample, the right leg was indicated as the dominant leg. There was no statistical difference when comparing the results of the right and left legs, or dominant and non-dominant (p>0.05 for all comparisons). However, the longest time was statistically greater than the average between the three repetitions, for any of the legs (p<0.001 for all). The intraclass correlation coefficient (ICC) between the three repetitions for the dominant leg was 0.72 (0.61 to 0.81) and for the non-dominant leg was 0.53 (0.39 to 0.66). The factors associated with the test result with statistically significant correlations were mainly the ICC score, and the TUG and 1MSTS results, regardless of which SLS result was considered (low to fair correlations). Conclusion: It is concluded that although there is no difference between the SLS results in the right and left legs, or dominant and non-dominant legs, in elderly people with COPD, the better reliability in the dominant leg suggests that only this leg needs to be evaluated. The associated factors were similar between the legs, represented mainly by the severity of comorbidities, dynamic balance and functional exercise capacity, which reinforces that only one leg needs to be evaluated.